RESPONS STRUKTUR BANGUNAN BERDASARKAN SPEKTRA GEMPA INDONESIA UNTUK IBUKOTA PROVINSI DI PULAU SUMATERA - Jingga, Hendra; Suryanita, Reni; Yuniarto, Enno (Proceedings ACES (Annual Civil Engineering Seminar), 2015)
Sumatera Island is a very active seismic area in Indonesia, which is crossed by the infamousPacific Ring of Fire. The western side of Sumatera Island suffers more from the groundshaking due to its closer distance to the epicenter. Combined with huge coverage of soft soil,building structures built on this island may experience excessive deformation and eventuallycollapse in a brittle way. For high-rise reinforced concrete (RC) building, the impact is evenmore devastating and may endanger its occupants. Due to these facts, this study aims toanalyze the deformation characteristic (story-drift) of high-rise RC building under earthquakeloading in Sumatera Island. Modal response spectrum analysis is performed to compute themaximum story-drift of three RC building models (10 story, 15 story, and 20 story) used in thisstudy. The seismic acceleration response spectrum function is derived from the lastestIndonesia’s Seismic Hazard Map (2010) and SNI 1726-2012. Eight capital cities in SumateraIsland and three soil conditions (soft, medium, and hard soil) are selected to generate 24seismic acceleration response spectrum functions. Combined with three RC building modelvariations, 72 story-drift data are obtained for each X and Y horizontal direction. Based on theanalysis result, taller buildings in soft soil condition are at greater risk to experience excessivedeformation due to seismic loading. Seismic locations in the western side of Sumatera Island isalso observed to exhibit higher seismic hazard compared to central and eastern side ofSumatera Island.Keywords: artificial neural network (ANN), earthquake, modal response spectrum analysis,structural response, Sumatera Island